1993
DOI: 10.4141/cjas93-027
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 (IGF-1) gene expression in porcine ovarian tissue

Abstract: A study was conducted to demonstrate IGF-1 gene expression in porcine ovarian tissue. Using northern blot analysis, IGF-1 messenger ribonucleic acid (mRNA) transcripts could not be consistently detected in total RNA. Authentic mRNA transcripts were detected in polyadenylated RNA-enriched RNA with sizes of 8.0, 3.6 and 2.3 bases, and possibly 0.8–1.1 kbases. Key words: Ovary, IGF-1, pig, mRNA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Ribonuclease protection assay IGF-I mRNA in all samples was measured in an RNase protection assay procedure as described by Gilman (1987) but with modifications as follows. As a human IGF-I riboprobe has already been used in our laboratory to establish the expression of the IGF-I gene in the pig ovary by Northern blot analysis (Charlton et al 1993), we used an available human exon 3 IGF-I riboprobe to develop a heterologous human-pig RNase protection assay. Duplicate ali¬ quots of 50 pg sample total RNA were hybridized overnight with 5 x 106 d.p.m.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ribonuclease protection assay IGF-I mRNA in all samples was measured in an RNase protection assay procedure as described by Gilman (1987) but with modifications as follows. As a human IGF-I riboprobe has already been used in our laboratory to establish the expression of the IGF-I gene in the pig ovary by Northern blot analysis (Charlton et al 1993), we used an available human exon 3 IGF-I riboprobe to develop a heterologous human-pig RNase protection assay. Duplicate ali¬ quots of 50 pg sample total RNA were hybridized overnight with 5 x 106 d.p.m.…”
Section: Animalsmentioning
confidence: 99%
“…In order to reduce RNA degradation within ovarian tissue, follicles were removed in as short a time as possible (approximately 2 min per ovary) by coarse dissection of individual follicles from the frozen ovary and immediate sub¬ mersion of the follicular tissue in liquid nitrogen. Total RNA was isolated from each ovarian sample, and from a 0-5 g sample of liver from the same animal, using the guanidine isothiocyanate/caesium chloride procedure described by Chirgwin et al (1979) with modifications as described by Charlton et al (1993). The quantity and purity of the RNA obtained was determined by ultraviolet spectrophotometry at 260 and 280 nm.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, IGF-1 exerts multiple physiologic effects on the systemic vasculature through endocrine, autocrine or paracrine mechanisms [2]. Many studies have reported that IGF-1 widely exists in mammalian ovarian tissues and is indispensable to follicle growth [3,4,5]. For example, the development of ovaries from the mouse deleted IGF-1 gene was incomplete, with the follicles arresting at the pre-antral or early antral stage and the mitotic abilities of granulosa cells presenting as weak [6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, follicular IGF-1 levels were elevated above peripheral levels and there was no correlation between the two, implying de novo synthesis of IGF-1 in the follicle. Indeed, the ovarian follicle of the prepubertal gilt does synthesize IGF-1 (Charlton et al 1993a) and there appears to be differential regulation of hepatic (and, consequently, peripheral) and ovarian (local) IGF-1 synthesis ( Fig. 3b; Charlton et al 1993b).…”
Section: Nutritional Modulation Of Ovarian Functionmentioning
confidence: 99%